Pemberdayaan Masyarakat Pesisir Padang melalui Inovasi Pengolahan Produk Olahan Ikan dalam Upaya Penguatan Ekonomi Masyarakat Ulak Karang Selatan - Rahmi, Elvi; Susanti, Dessi; Rahmidani, Rose; Sofya, Rani; Hayati, Annur Fitri; Armiati, Armiati; Cerya, Efni (Universitas Pahlawan Tuanku Tambusai, 2025)
The coastal area of Padang City, particularly Ulak Karang Selatan, possesses abundant fisheries resources. However, local fishing communities still face challenges such as limited product innovation, weak branding, inadequate financial management skills, and minimal use of digital marketing. This community service program aimed to empower the Kelompok Pengolah dan Pemasar (POKLAHSAR) through training in fisheries product innovation, particularly the processing of fish into value-added products such as dim sum and batagor. The program was complemented by capacity-building activities in digital marketing, business financial management, and the design of product logos and packaging. The activities were conducted using a participatory approach through counseling, demonstrations, hands-on practice, and evaluation. The results indicated a significant improvement in participants’ skills, particularly in production, financial recording, and digital marketing strategies. Furthermore, participant evaluation revealed a high level of satisfaction, with an average achievement of over 90% across all indicators. This program not only enhanced the economic capacity of fishing households but also contributed to the achievement of the Sustainable Development Goals (SDGs).